(untitled) (Asian Journal of Medical and Biological Research, 2020)
Repeat breeding is one the most common reproductive disorders that hinders favorable productivity in domestic animals. Repeat breeding in dairy cows not only affects the fertility of the cattle to a considerable extent but also incurs great economic loss to the farmer. Biochemical profile can indicate the nutritional status and help in diagnosis and management of infertility in animals. Present study explores the implication of some biochemical parameters (total protein, bilirubin and some macro minerals as calcium, inorganic phosphorus and magnesium) on normal cyclic breeding process of Bangladeshi dairy cows. Current observation indicates that the lower calcium, inorganic phosphorus and magnesium concentrations might be associated with the ovulatory disturbances in repeat breeder cows. On the other hand, total protein and bilirubin do not play a significant role in causing repeat breeding problem in those cows. Thus, this study provides supportive evidence about the importance of calcium, inorganic phosphorus and magnesium in the resumption of repeat breeding condition. Asian J. Med. Biol. Res. June 2020, 6(2): 305-310